Highly Reproducible Ag NPs/CNT-Intercalated GO Membranes for Enrichment and SERS Detection of Antibiotics - Qu, Lu−Lu; Liu, Ying-Ya; Liu, Ming-Kai; Yang, Guo-Hai; Li, Da-Wei; Li, Hai-Tao (ACS applied materials & interfaces, 2016)
The increasing pollution of aquatic environments by antibiotics makes it necessary to develop efficient enrichment and sensitive detection methods for environmental antibiotics monitoring. In this work, silver nanoparticles and carbon nanotube-intercalated graphene oxide laminar membranes (Ag NPs/CNT-GO membranes) were successfully prepared for enrichment and surface-enhanced Raman scattering (SERS) detection of antibiotics. The prepared Ag NPs/CNT-GO membranes exhibited a high enrichment ability because of the π–π stacking and electrostatic interactions of GO toward antibiotic molecules, which enhanced the sensitivity of SERS measurements and enabled the antibiotics to be determined at sub-nM concentrations. In addition, the nanochannels created by the intercalation of CNTs into GO layers resulted in an 8-fold enhancement in the water permeance of Ag NPs/CNT-GO membranes compared to that of pure GO membranes. More importantly, the Ag NPs/CNT-GO membranes exhibited high reproducibility and long-term stability. The spot-to-spot variation in SERS intensity was less than 15%, and the SERS performance was maintained for at least 70 days. The Ag NPs/CNT-GO membranes were also used for SERS detection of antibiotics in real samples; the results showed that the characteristic peaks of antibiotics were obviously recognizable. Thus, the sensitive SERS detection of antibiotics based on Ag NPs/CNT-GO offers great potential for practical applications in environmental analysis.